2007
DOI: 10.1001/archinte.167.9.966
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' Understanding of the Regulation of Dietary Supplements

Abstract: Background: After passage of the Dietary Supplement Health and Education Act, herbs and other supplements were allowed to be sold to the public without Food and Drug Administration (FDA) approval or premarket evaluation. Data suggest that many people are unaware of this lack of governmental oversight and may rely on their physicians for education in this arena. This study was designed to evaluate physicians' level of understanding of dietary supplement regulation and the adverse event reporting process and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 17 publications
1
35
0
1
Order By: Relevance
“…At the same time, producers often fail to include any information on a recommended daily dose of the manufactured supplement which is a clear infringement of EU law and indicates local problems with an enforcement problem . Importantly, studies have shown that some physicians may be unaware of the biological properties of FS (Kemper et al 2006;Ashar et al 2007) while consumers may mistakenly consider these products as drugs designed to treat diseases (Wierzejska et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…At the same time, producers often fail to include any information on a recommended daily dose of the manufactured supplement which is a clear infringement of EU law and indicates local problems with an enforcement problem . Importantly, studies have shown that some physicians may be unaware of the biological properties of FS (Kemper et al 2006;Ashar et al 2007) while consumers may mistakenly consider these products as drugs designed to treat diseases (Wierzejska et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…[58][59][60][61][62] Unless health benefits can be clearly demonstrated by well-designed, well-executed studies, our findings suggest that the potential for harm from use of some herbal supplements may exceed the benefit. Unfortu- Moreover, 37% of physicians surveyed across the US were unaware that supplements do not require FDA pre-market approval for safety and efficacy, 64 indicating increased training and CME on this topic are needed. It is hoped that the FDA's current good manufacturing practices (CGMPs), which by 2010 require all manufacturers to evaluate supplement identity, purity, strength, and composition, will lead to safer supplements.…”
Section: Discussionmentioning
confidence: 99%
“…Also, guidelines for conducting in vitro and in vivo studies and their relevance for clinical safety data are defined. Apparently, these initiatives are necessary since efficacy and safety of dietary supplements and herbals is poorly documented, and the awareness of consumers and health professionals towards nutritional supplements as a potential source of health damage is low [4,47].…”
Section: Productmentioning
confidence: 99%